A global review of national influenza immunization policies: Analysis of the 2014 WHO/UNICEF Joint Reporting Form on immunization. Issue 45 (26th October 2016) - Ortiz, Justin R.; Perut, Marc; Dumolard, Laure; Wijesinghe, Pushpa Ranjan; Jorgensen, Pernille; Ropero, Alba Maria; Danovaro-Holliday, M. Carolina; Heffelfinger, James D.; Tevi-Benissan, Carol; Teleb, Nadia A.; Lambach, Philipp; Hombach, Joachim
Abstract: Introduction: The WHO recommends annual influenza vaccination to prevent influenza illness in high-risk groups. Little is known about national influenza immunization policies globally. Material and Methods: The 2014 WHO/UNICEF Joint Reporting Form (JRF) on Immunization was adapted to capture data on influenza immunization policies. We combined this dataset with additional JRF information on new vaccine introductions and strength of immunization programmes, as well as publicly available data on country economic status. Data from countries that did not complete the JRF were sought through additional sources. We described data on country influenza immunization policies and used bivariate analyses to identify factors associated with having such policies. Results: Of 194 WHO Member States, 115 (59%) reported having a national influenza immunization policy in 2014. Among countries with a national policy, programmes target specific WHO-defined risk groups, including pregnant women (42%), young children (28%), adults with chronic illnesses (46%), the elderly (45%), and health care workers (47%). The Americas, Europe, and Western Pacific were the WHO regions that had the highest percentages of countries reporting that they had national influenza immunization policies. Compared to countries without policies, countries with policies were significantly more likely to have the following characteristics: to be high or upper middle income ( p < 0.0001); to have introduced birth dose hepatitis B virus vaccine ( p < 0.0001), pneumococcal conjugate vaccine ( p = 0.032), or human papilloma virus vaccine ( p = 0.002); to have achieved global goals for diphtheria-tetanus-pertussis vaccine coverage ( p < 0.0001); and to have a functioning National Immunization Technical Advisory Group ( p < 0.0001). Conclusions: The 2014 revision of the JRF permitted a global assessment of national influenza immunization policies. The 59% of countries reporting that they had policies are wealthier, use more new or under-utilized vaccines, and have stronger immunization systems. Addressing disparities in public health resources and strengthening immunization systems may facilitate influenza vaccine introduction and use.